Search for gluino-mediated bottom squark production in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2009)
We report on a search for the supersymmetric partner of the bottom quark produced from gluino decays in data from 2.5fb-1 of integrated luminosity collected by the Collider Detector at Fermilab at s=1.96TeV. Candidate events are selected requiring two or more jets and large missing transverse energy. At least two of the jets are required to be tagged as originating from a b quark to enhance the sensitivity. The results are in good agreement with the prediction of the standard model processes, giving no evidence for gluino decay to bottom squarks. This result constrains the gluino-pair-production cross section to be less than 40 fb at 95% credibility level for a gluino mass of 350GeV/c2. © 2009 The American Physical Society.